To solve the system of equations, we can use the method of substitution.
Since the second equation is already solved for x, we can substitute that expression into the first equation.
x - 6y = 22
x = 6y + 22
Now we can substitute this expression for x into the first equation:
5(6y + 22) + 2y = 14
Expand and simplify:
30y + 110 + 2y = 14
32y + 110 = 14
32y = 14 - 110
32y = -96
y = -96/32
y = -3
Now we can substitute this value of y back into the second equation to solve for x:
x - 6(-3) = 22
x + 18 = 22
x = 22 - 18
x = 4
Therefore, the solution to the system of equations is (x, y) = (4, -3).
Solve the system of equations.%0D%0A5x+2y=14%0D%0Ax−6y=22(1 point)%0D%0A(, )
1 answer